Metabolic Syndrome and Breast Cancer Molecular Subtypes: An Observational Patient Study - Dafina Ademi-Islami; Suzana Manxhuka-Kerliu; Dhurata Tarifa-Koroveshi; Rozafa Koliqi; Blerim Mujaj (Breast Cancer: Basic and Clinical Research, 2022)
Background: Breast cancer molecular subtypes share various prognostic profiles, and luminal A molecular subtypes have a better prognosis compared with other molecular subtypes. However, whether metabolic syndrome or individual risk factors of metabolic syndrome influence on the development of molecular subtype remains elusive. We aimed to assess the association between metabolic syndrome risk factors and breast cancer molecular subtypes among patients with metabolic syndrome in a clinical setting. Methods: In total, 101 breast cancer patients with mean age, 58.4 ± 8.5 years, and overt metabolic syndrome prospectively were recruited. Immunohistochemistry procedure was used to determine molecular subtypes. Assessment of clinical, biochemical, and anthropometric parameters was performed. Logistic regression analysis was used to assess the relationship between risk factors and breast cancer molecular subtypes categories. A similar approach was used to assess the relation between breast cancer molecular subtypes and menopause. Results: Comparison of metabolic syndrome individual risk factors according to breast cancer molecular subtypes no statistical difference was found for systolic ( P  = .33) and diastolic blood pressure ( P  = .17), fasting glucose ( P  = .77), triglycerides ( P  = .62), high-density lipoprotein ( P  = .33), body mass index ( P  = .87), and waist circumference ( P  = .81). A positive trend was found between high-density lipoprotein and HER2+. No association was found with other risk factors. Moreover, an association was found between HER2+ categories and menopause. Conclusion: In breast cancer patients with metabolic syndrome, we observed an increased trend between high-density lipoprotein and HER2+ molecular subtype, suggesting that underlying dyslipidemia may favor poor prognosis. HER2+ was associated with menopause which may influence further expression of HER2+ .